Implementasi Strategi Pelayanan Bagian Umum Rumah Tangga dalam Pengelolaan Peminjaman Ruangan dan Sarana Prasarana Pemerintahan - Eka Firdatul Fauziyah; Magda Faradiba Mauludia Agung (CV. Ulil Albab Corp, 2026)
Internal government services play an important role in supporting the implementation of regional governmental functions. One form of internal service is the management of room and government facilities lending carried out by the General Affairs and Household Division of the Regional Secretariat of Gresik Regency. This study aims to analyze the implementation of service strategies in managing the lending of rooms and government facilities and to identify supporting and inhibiting factors. This research employed a descriptive qualitative approach using observation, informal interviews, and documentation studies conducted during an internship program. The results indicate that service strategies have been implemented through clear procedures, adequate internal coordination, and staff responsiveness. However, service effectiveness is still constrained by manual recording systems and limited human resources. The study concludes that the implementation of service strategies is fairly effective and requires strengthening through system digitalization, human resource capacity building, and improved archival management to support accountable governance. Keywords: service strategy, internal service, facilities management, general affairs division, regional secretariat